Determinasi Happiness Index Melalui Pendekatan Sosial Ekonomi - Puspatriani Damayanti; Dedy Yuliawan (Shofanah Media Berkah, 2023)
This study breaks down how still up in the air in Indonesia through a financial methodology. This information investigation technique utilizes different relapse which is helpful for deciding the bearing of the connection between the reliant and free factors. This examination technique utilizes Eviews 12 programming. The information hotspot for this exploration utilizes auxiliary information from the authority site of the Focal Insights Organization (BPS). This exploration utilizes cross sectional information type. The factors of training, lodging conditions and resources as well as friendly relations significantly affect the joy file in Indonesia in 2021. The factors of work and family congruity affect the Satisfaction File in Indonesia in 2021. The utilization and wellbeing factors have a huge positive however not massive impact on Joy List in Indonesia in 2021